Wire-Mesh 16 Ã— 16 Capacitance Sensor for Analysis of Capacitance Distribution on Cylindrical Pipe - Sujiwa, Akbar; Endarko, Endarko (Institut Teknologi Sepuluh Nopember, 2018)
The wire-mesh sensor is an intrusive sensor device that uses for generating 2-dimensional (2D) images of fluid flow. Sensors made of 2 layers copper wires, transmitter, and receiver, that perpendicular each other. The wire-mesh sensor will directly to measure the value of inductance or capacitance at the crossing wire. There are 208 data measurements in 16 Ã— 16 cylindrical wire-mesh sensors. All data measurement then processed by Python software to obtain a 2D image of the capacitance distribution. Experiment results show the inhomogeneous distribution of capacitance that occurs in the wire-mesh sensor. Three types of liquids, distilled water, tap water and salt solution, showed circular pattern of capacitance distribution, with the highest capacitance value being in the central area of the image, while at edge area has a lower capacitance value than the central area